Computational phraseology - Corpas Pastor, Gloria; Colson, Jean-Pierre (IVITRA research in linguistics and literature ;, 2020)
"Whether you wish to deliver on a promise, take a walk down memory lane or even on the wild side, phraseological units (also often referred to as phrasemes or multiword expressions) are present in most communicative situations and in all world's languages. Phraseology, the study of phraseological units, has therefore become a rare unifying theme across linguistic theories. In recent years, an increasing number of studies have been concerned with the computational treatment of multiword expressions: these pertain among others to their automatic identification, extraction or translation, and to the role they play in various Natural Language Processing applications. Computational Phraseology is a comparatively new field where better understanding and more advances are urgently needed. This book aims to address this pressing need, by bringing together contributions focusing on different perspectives of this promising interdisciplinary field"--